Incidence and non-drug aetiologies of aplastic anaemia in Thailand - Surapol Issaragrisil (2018)
A population-based, case-control study of aplastic anaemia has been conducted in Thailand since 1989. Up to December 1994, the overall annual incidence was 3.9/106 in Bangkok, 5.0/106 in Khonkaen and 3.0/106 in Songkla. In Bangkok, the incidence peaked in 2 age groups (at 15-24 yr and ≤60 yr), whereas in Khonkaen and Songkla there was a consistent increase in incidence with increasing age. The results of case-control analyses for non-drug risk factors indicate a strong inverse association with socio-economic status present in all 3 areas; a strong association with grain farming in the 2 rural areas that does not appear to be explained by pesticides; an association with occupational exposure to solvents in Bangkok; and a positive association with hepatitis A seropositivity.